Supersaturated gas bubble formation across an orifice - Ban, Z.H. (Trans Tech Publications Ltd, 2014)
A solution could be made supersaturated when the physical conditions was altered. The supersaturated gas would form bubble to bring the solution back to the equilibrium condition. Bubble would first nucleated and then growth in the solution. This work was aimed to simulate the bubble formation across an orifice, with sufficient pressure drop. The CO2 was assumed to be made saturated at 6 atm in water, and formed bubble when the solution flowed across the orifice. As the CO2 bubble formed across the orifice, the volume of the CO2 gas occupied almost the whole space in the orifice. The mass of the dissolved CO2 in water had decreased too as it had transferred into gas CO2. Â© 2014 Trans Tech Publications, Switzerland.